2023
DOI: 10.1021/acs.langmuir.3c01871
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Plant Protein Nanoparticles Prepared by Cation-Exchange Resins for Stabilization of Pickering Emulsions

Pengcheng Xu,
Chen Lin,
Xuyuan Li
et al.

Abstract: Our understanding of the microstructure of many plant proteins is based on the ancient and conventional methods of alkali extraction and acid precipitation, which generate considerable amounts of NaCl causing salting-out effects and aggregation of their molecules. In this study, monodisperse rice protein (RP) nanoparticles were prepared using cation-exchange resins that release H+ and absorb Na+, thus avoiding the generation of NaCl during neutralization of the alkali extracts. The generated RP nanoparticles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…TEM showed that RPs had a uniform spherical morphology with sizes in the range of tens of nanometers (Figure a) . ATPs featured rod structures with a radius of 5–10 nm and a length of several micrometers, offering a specific surface area of about 100–216 m 2 ·g –1 (Figure b) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM showed that RPs had a uniform spherical morphology with sizes in the range of tens of nanometers (Figure a) . ATPs featured rod structures with a radius of 5–10 nm and a length of several micrometers, offering a specific surface area of about 100–216 m 2 ·g –1 (Figure b) .…”
Section: Resultsmentioning
confidence: 99%
“…After magnetic stirring at 990 rpm for 1 h, the dispersion was treated with cation exchange resin that released H + in exchange for absorption of Na + in order to adjust the pH to 7. This neutralized the basicity without the generation of NaCl and avoided aggregation of RPs, thus affording the formation of uniform RP nanoparticles …”
Section: Methodsmentioning
confidence: 99%